2015
DOI: 10.1038/nature14888
|View full text |Cite
|
Sign up to set email alerts
|

BET inhibitor resistance emerges from leukaemia stem cells

Abstract: Bromodomain and extra terminal protein (BET) inhibitors are first-in-class targeted therapies that deliver a new therapeutic opportunity by directly targeting bromodomain proteins that bind acetylated chromatin marks1,2. Early clinical trials have shown promise, especially in acute myeloid leukaemia3, and therefore the evaluation of resistance mechanisms is crucial to optimize the clinical efficacy of these drugs. Here we use primary mouse haematopoietic stem and progenitor cells immortalized with the fusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
405
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(446 citation statements)
references
References 42 publications
26
405
2
3
Order By: Relevance
“…S8D) in line with H23 cells undergoing apoptosis and slower cell proliferation rate (Figure 5(b)). The main components of canonical Wnt/β-catenin signaling are reported to be modulated by JQ1 [6,29,30] and in H23 cells, WNT2, WNT5A, and the mediator of Wnt signaling (LEF1 and TCF genes) were downregulated, while β-catenin encoded by CTNNB1 was only slightly affected (Fig. S8B).…”
Section: Resultsmentioning
confidence: 99%
“…S8D) in line with H23 cells undergoing apoptosis and slower cell proliferation rate (Figure 5(b)). The main components of canonical Wnt/β-catenin signaling are reported to be modulated by JQ1 [6,29,30] and in H23 cells, WNT2, WNT5A, and the mediator of Wnt signaling (LEF1 and TCF genes) were downregulated, while β-catenin encoded by CTNNB1 was only slightly affected (Fig. S8B).…”
Section: Resultsmentioning
confidence: 99%
“…While our study was underway, several other groups reported alternative mechanisms of BETi resistance in other cancer lines (39)(40)(41)(42)(43). Although the details of the specific adaptive pathways vary across cell types, a common feature of BETi resistance appears to be reactivation of BRD4-dependent target genes.…”
Section: Discussionmentioning
confidence: 99%
“…GSEA transcriptome analysis by Fong et al [5] revealed upregulation of the Wnt/β-catenin signaling pathway, which has also been implicated in cancer stem cell maintenance [6]. Importantly, they showed that inhibition of the Wnt pathway restored the more mature myeloid phenotype, survival advantage conferred by I-BET in resistant clones, and abrogation of Myc expression.…”
mentioning
confidence: 99%
“…The resistant cell lines generated by Fong et al [5] showed a loss of myeloid lineage markers Gr1 and CD11b and an increase in tumor initiating capacity in limiting dilution assays in vivo. This raised the possibility that resistance to I-BET emerges from a leukemic stem cell (LSC) compartment.…”
mentioning
confidence: 99%
See 1 more Smart Citation